The Gambia : Poverty Reduction Strategy Paper; Second Annual Progress Report. (IMF Staff Country Reports; Country Report, 2006)
The economic performance has been positive as tight macroeconomic policies prevailed, helped by a remarkable revenue mobilization effort. None of the key indicator targets were met. Fiscal performance improved, but there was an increase in the overall fiscal deficit. Monetary policy was also less expansionary. Efforts were sustained to strengthen the justice delivery system. The long-term goal is to eradicate poverty by significantly increasing the national income, through stable economic growth, and reducing income and non-income inequalities through specific poverty-reduction priority interventions.